Wintering Steppe Eagle in Hurghada (Egypt) from 2016 till 2022 - Mohamed I. Habib (Пернатые хищники и их охрана)
The East African-Eurasian flyway is one of the most important routes for migratory soaring birds in the world. Each spring and autumn 37 species of migratory soaring birds navigate this flyway, with over a million birds passing through the larger bottlenecks.